Estrategia educativa en salud bucal Camaleón sonriente cuida tus dientes para escolares con y sin discapacidad visual (2022)
Introduction:Education strategies should be inclusive to all types of populations, mainly with children whom they may have conditions of mental and physical disables. The assessment of social determinants might always accompany education in oral hygiene; likewise, education strategies are tools that contribute to improving knowledge; without that will be a determinant factor in the attitude and well practice of oral hygiene; nevertheless, it is the first step to do it. Objective: To determine the effectiveness of the educational strategy in oral health called the smiling chameleon for children with and without visual impairment in the first semester of 2022.